Increased immunological markers in female adolescents with non-suicidal self-injury - Kindler, Jochen; Koenig, Julian; Lerch, Stefan; Venne, Patrice van der; Resch, Franz; Kaess, Michael (Journal of affective disorders, 2022)
Background - Nonsuicidal self-injury (NSSI) is a prevalent health problem among adolescents and commonly associated with psychological stressors such as childhood maltreatment and comorbid psychiatric disorders (e.g., depression). There is evidence that alterations of immunological markers may occur in the context of both environmental stress and psychopathological development. - Method - Here, we investigated differences in plasma/serum leukocytes, cortisol, c-reactive protein and interleukin-6 in a large sample of female adolescents with NSSI (n=155) and healthy controls (HC, n=42). Further, we assessed correlations between inflammatory markers, depression severity and the severity of childhood maltreatment. - Results - The absolute number of leukocytes and the leukocyte/cortisol ratio (adjusted for body mass index and smoking) were significantly higher in NSSI as compared to HC, whereas interleukin-6 and CRP levels did not differ significantly between groups. Childhood maltreatment scores were significantly correlated with the leukocyte/cortisol ratio and depression severity was significantly correlated with both, absolute leukocyte numbers and the leukocyte/cortisol ratio. - Conclusions - Our results suggest that an immune activation can be detected in female adolescents with NSSI. Depression and childhood maltreatment, which are commonly reported in NSSI, may potentially underlie immune activation and partially explain group differences.